Answer :


Using formula ,






Using ,





Using , since A + B + C = π



And, cos(π – A ) = -cosA




Using , cos2A = 1 – 2sin2A




since A + B + C = π


and Using ,





Using , since A + B + C = π




= R.H.S


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If A + B + C = π,RS Aggarwal - Mathematics

If A + B + C = π,RS Aggarwal - Mathematics